Population Redistribution Trends in Nonmetropolitan America, 2010 to 2021. (16th November 2022) - Johnson, Kenneth M.
Abstract: Given the turbulent conditions of the early 21st century and the release of data from the 2020 Census, it is an appropriate time to examine contemporary population redistribution trends in nonmetropolitan America. Analysis centers on the major demographic components of population change: migration; and natural increase. The analysis demonstrates that the turbulent economic, social, and now epidemiological conditions of recent years altered traditional demographic trends in nonmetropolitan America. For the first time in history, nonmetropolitan America lost population between 2010 and 2020 because of shifts in migration trends and diminishing natural increase. In contrast, post‐censal population estimates suggest that nonmetropolitan population gains exceeded those in metropolitan areas for the first time in 50 years between 2020 and 2021. The recent widespread nonmetropolitan population increases are the result of substantial net migration gains that offset the growing natural decrease fostered by COVID‐19. Sustained net migration gains in nonmetro areas provides a demographic lifeline to many counties that would otherwise face depopulation because of accelerating natural decrease. Whether these migration patterns can be sustained remains to be seen.